Protective Effect of Adipose-Derived Mesenchymal Stem Cell Secretome against Hepatocyte Apoptosis Induced by Liver Ischemia-Reperfusion with Partial Hepatectomy Injury - Zhihui Jiao; Yajun Ma; Yue Wang; Tao Liu; Qianzhen Zhang; Xiaoning Liu; Chenxi Piao; Boyang Liu; Hongbin Wang (Stem Cells International)
Ischemia-reperfusion injury (IRI) is an inevitable complication of liver surgery and liver transplantation. Hepatocyte apoptosis plays a significant role in the pathological process of hepatic IRI. Adipose-derived stem cells (ADSCs) are known to repair and regenerate damaged tissues by producing bioactive factors, including cytokines, exosomes, and extracellular matrix components, which collectively form the secretome of these cells. The aim of this study was to assess the protective effects of the ADSCs secretome after liver ischemia-reperfusion combined with partial hepatectomy in miniature pigs. We successfully established laparoscopic liver ischemia-reperfusion with partial hepatectomy in miniature pigs and injected saline, DMEM, ADSC-secretome, and ADSCs directly into the liver parenchyma immediately afterwards. Both ADSCs and the ADSC-secretome improved the IR-induced ultrastructural changes in hepatocytes and significantly decreased the proportion of TUNEL-positive apoptotic cells along with caspase activity. Consistent with this, P53, Bax, Fas, and Fasl mRNA and protein levels were markedly decreased, while Bcl-2 was significantly increased in the animals treated with ADSCs and ADSC-secretome. Our findings indicate that ADSCs exert therapeutic effects in a paracrine manner through their secretome, which can be a viable alternative to cell-based regenerative therapies.